Os Kujubim e os bichos-de-pena: uma etnografia multiespecífica das relações entre humanos e não-humanos no vale do Guaporé, Rondônia - Sanchez, Gabriel (2019)
Initially, this was a research about the “classifications” of beings that our western biology denominate “birds” from the pratical and semiotic perspectives of the Kujubim indigenous peoples (Rondônia) – a group until here, unknown by ethnology in the Lowlands of South America. However, by conducting a six-month field research with this people and acess various native categories through a series of a controlled equivocation and dissonances between scientific and Kujubim categories, what we find and know were not “birds” but “bichos-de-pena”. Therefore, the main objective of this work is to produce a “multispecies etnhography” around the pratices, knowledge and relations of this people with the “bichos-de-pena” and, in this sense, this is also an “ethnography of the relations”. It is relations, as we will see, that are enable Kujubim to “rate” the “bichos-de-pena”. In the people there are no “classification system”, either conditioning categories and define beigs permanently, but before relations (between beings and between categories) that allow them to transit, or, we suggest, “transform” in the world and the Kujubim thought. The “transform” does not have the meaning attributed to metamorphosis, it’s about an aspect where it can be said that everything is (está), and nothing is (é): among the Kujubim, “bichos-de-pena” never are, in fact, in the sense of condition, but always tend to be or are, in the sense of a state: there, nothing is (é), everything is (está) in permanently becoming, everything is transqualitative, everything is, after all and as we suggested, “anti-taxonomic”.